AGAMA DAN PROBLEMATIKA MASYARAKAT: FUNGSI TASAWUF DALAM PENDIDIKAN, SOSIAL DAN AKHLAK - A. Samad, Sri Astuti; Nurdin, Abidin; Samad, Munawwarah; Gade, Fihriani (FISIP Universitas Malikussaleh, 2024)
Islam entered the archipelago peacefully brought by Sufi scholars and is influential to this day. Sufism is a dimension of Islamic teachings that is able to answer the problems of society from the past to the present. Sufi scholars also fought against colonialism supported by Sufi brotherhood or tariqa in which there was a concept of obedience to the teacher. The reformulation of classical Sufism which is individual, personal, is important enough to become a communal collective. This article is a qualitative study analyzed using the perspective of sociology of religion. Today, Sufism remains important in various aspects of education, social movements, and moral improvement. If using the perspective of sociology of religion, Sufism is able to provide spirit and strength to humans so that Sufism values transform for the better. The values of Sufism in question are for example, qana'ah, patience, gratitude which provide solutions to the problems of human life. Not only limited to educational, social and moral improvement aspects but more than that.Islam masuk ke Nusantara secara damai dibawa oleh para ulama sufi dan berpengaruh sampai saat ini. Tasawuf merupakan dimensi ajaran Islam yang mampu menjawab problematika masyarakat sejak pada masa lalu sampai sekarang. Ulama sufi juga melakukan perlawanan terhadap kolonialisme yang didukung oleh persaudaraan sufi atau tarekat yang di dalamnya terdapat konsep ketaatan pada guru. Reformulasi tasawuf klasik yang bersifat individual personal cukup penting menjadi kolektif komunal.Artikel ini merupakan studi kualitatif yang dianalisis dengan menggunakan perspektif sosiologi agama. Saat ini kemudian bangsa Indonesia semakin maju sufisme tetap menjadi sesuatu yang urgen dalam berbagai aspek pendidikan, gerakan sosial, dan perbaikan akhlak. Jika menggunakan perspektif sosiologi agama, bahwa tasawuf mampu memberikan spirit dan kekuatan pada manusia sehingga nilai-nilai tasawuf bertransformasi ke arah yang lebih baik. Nilai-nilai tasawuf yang dimaksud misalnya, qanaah, sabar, syukur yang memberikan solusi problematika kehidupan manusia. Tidak hanya sebatas aspek pendidikan, social dan perbaikan akhlak akan tetapi lebih dari itu.